KAJIAN USAHA HIDANGAN ISTIMEWA KAMPUNG (HIK) DI KABUPATEN BOYOLALI - Affandi, Haris Akhmad; Sudarmadi, Sudarmadi (Riset Manajemen dan Akuntansi, 2019)
This study aimed to determine the effect of capital, long effort, time business, labor, and the distance effort against street food stall (HIK trader) profits in Boyolali. In addition, this study aims to examine whether there is a significant difference between the variable status of the business and location of the business to the HIK trader profits in Boyolali for a month. The data used in this study are primary data analysis tool that is used by multiple linear regression, the two mean difference test independent and different test one-way ANOVA. There is a single dependent variable is profit and seven independent variables is the variable capital, long effort, time effort, the amount of labor, business status, and location of the business. Results of regression with a significance of 10% indicates that the capital, experience , time business, labor, and the distance effort positively affects on traders' profits, while the time of the attempt shows a negative effect on HIK trader profits in Boyolali. From the test results mean difference two independent and one-way ANOVA showed that the status of the business does not have a significant difference to the traders' profits, while the location of the business has a significant difference to the HIK trader profits in Boyolali. Advice can be given from this research is that the government must pay attention to the existence of a stall HIK.